Increased abundance of nitrogen transforming bacteria by higher C/N ratio reduces the total losses of N and C in chicken manure and corn stover mix composting - Zhang, WenMing; Yu, ChenXu; Wang, XuJie; Hai, Long (Bioresource technology, 2020)
•Succession of dominant bacteria of different C/N ratio were characterized.•Higher C/N promoted the relative abundance of nitrogen fixing bacteria.•Higher C/N compressed the denitrifying bacteria.•Adjustment to C/N ratio could improve compost quality. The aim of this work was to investigate how the initial C/N ratio during composting of chicken manure/corn stover mix affected the succession of dominant bacteria in the mix which led to the reduction of the total losses of N and C in the composting process. 16S rDNA sequencing indicated that the succession of predominant bacteria was significantly affected by the temperature and the initial C/N ratio during composting. Redundancy analysis showed that higher C/N appeared to promote the relative abundance of nitrogen fixing bacteria Thermoactinomyces, Planifilum, Flavobacterium, Bacillaceae, Pseudomonas,Sphingobacterium, Paenibacillus, Bacillus and Thermobifida, while compressing the denitrifying bacteria Pusillimonas, Ignatzschineria, Alcanivorax, Cerasibacillus, Truepera and Erysipelothrix. C/N ratio of 30:1 yielded the least C/N losses in the composting process, indicating that adjustment to the initial C/N ratio could affect nitrogen transforming bacteria to reduce the total losses of N and C and improve compost quality.